LAMA WAKTU PERENDAMAN EKSTRAK DAUN PEPAYA (Carica papaya L.) TERHADAP Argulus sp. PADA IKAN LELE (Clarias sp.) YANG DIPELIHARA DALAM TOPLES - Sri Ramadhana; Mukhlisah; Setyo Triadi (Fakultas Pertanian UVAYA Banjarmasin, 2026)
Catfish (Clarias sp.) is a highly popular freshwater aquaculture commodity in Indonesia, but production is often constrained by ectoparasite infestations, especially Argulus sp. This study aimed to investigate how different immersion durations of papaya (Carica papaya L.) leaf extract affect the detachment percentage of Argulus sp. on catfish (Clarias sp.) reared in jars. The research used an experimental design based on a Completely Randomized Design (CRD) with three treatments and three replications. The treatments tested were different immersion durations: A (20 minutes), B (40 minutes), and C (60 minutes) at a constant dosage of 1.0 g/L. The test fish were 8–10 cm in size and artificially infested with Argulus sp. at a density of 5 parasites per fish (10 parasites per jar). The primary parameter observed was the detachment percentage of Argulus sp., with supporting parameters including fish behavior and water quality. Analysis of variance (ANOVA) showed that immersion duration of papaya leaf extract had a significant effect (P<0.05) on the detachment percentage of Argulus sp. The highest detachment percentage was achieved in treatment C (60 minutes), with an average of 93.33%, followed by treatment B (40 minutes) at 76.67%, and the lowest in treatment A (20 minutes) at 56.67%. Behavioral observations during treatment showed clinical symptoms such as fish rubbing their bodies against the container walls, producing excessive mucus, and swimming vertically to the surface. However, no fish mortality occurred during the study. Water quality parameters (temperature, pH, DO, and ammonia) fluctuated slightly after treatment but remained within tolerable limits for catfish. In conclusion, a 60-minute immersion in 1.0 g/L papaya leaf extract is highly effective and recommended for controlling Argulus sp. infestations in catfish.